Methanolic extract of muntingia calabura leaves & aloe vera gel against selected pathogenic bacteria / Nur Aisyah Izzati Azman - Azman, Nur Aisyah Izzati (2017)
Muntingia calabura is the common roadside trees that had been neglected despite having medicinal values, while Aloe vera is the common plant used for antibacterial agent. Hence the purpose of this study is not only to identify and compare the effectiveness of antibacterial activity of both samples but also to provide ground prove of the advantages that can be taken from Muntingia calabura in terms of its antibacterial activity as alternative. From the study, there are significant difference of antibacterial activity between M. calabura and Aloe vera against the E. coli, S.typhi, S.aureus and B. subtilis as statistically analysis shows that p<0.05. The difference indiameters of zone of inhibition obtained through the study was also significant. It wasfound that methanolic extract of M. calabura showed greater inhibitions at 100mg/mL and 50 mg/mL as compared to the synthetic drug, streptomycin. From Table4.1, the highest mean value obtained at 100 mg/mL for E. coli, S. typhi, S. aureus andB.subtilis respectively was 3.33±5.77 mm, 12.00±1.00 mm, 9.00±7.81 mm, and16.67±6.03 mm whereas Aloe vera showed none. To conclude, M. calabura extractshowed promising potential as antibacterial agent compared to commonly used Aloevera for future drug development. It was also found that the extract was dose-dependent hence the studies can be done by using several higher dose concentrationsand adding the biochemistry test to the plant extract.